Relevansi Pancasila sebagai Ideologi Terbuka terhadap Fenomena Hedonisme Generasi Z di Ruang Digital - Syuratty Astuti Rahayu Manalu; Elsa Simanjuntak; Debora Gultom; Hariaty Manurung; Norlyn Pakpahan; Talenta N. D. Simatupang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Advances in digital technology and social media platforms have created new ways of interacting in society, especially among Generation Z, who were born and raised during the digital era. Social media not only functions as a communication tool, but also as a place to build self-image, compete for popularity, and gain social recognition. The emergence of digital hedonism can be seen through a culture of showing off, excessive consumption, and the desire to gain public exposure through viral content. This article explores the importance of Pancasila as a flexible ideology to overcome this phenomenon by linking several real examples, such as teenagers borrowing expensive items for content, young influencers displaying bank balances and cash, competition among digital creators, and prank content that harms others. These examples illustrate a decline in morals and a deviation from Pancasila values, ranging from a spiritual crisis to a loss of empathy in society. This study emphasizes that restoring Pancasila values is essential to shaping the character of Generation Z so that they do not fall into moral decline in the digital age. This recovery can be achieved through character education based on Pancasila, critical digital literacy, the role of the family, government regulations, and the strengthening of public ethical norms. Thus, Pancasila remains relevant as a moral and ideological guide that can overcome the challenges of globalization and instant culture.